Enhancing Good Governance in Kelurahan Panggungharjo: An Organizational Psychology Case Study in a Community Setting - Siti Mulyani; Elli Nur Hayati (Universitas Ahmad Dahlan, 2023)
Since 2014, Indonesia has enacted the Village Law, granting villages the authority to oversee the entire process of village development, aimed at fostering prosperous village communities. Despite this, research on achieving effective governance within village governments in Indonesia, through the combined lenses of Industrial Organizational Psychology (PIO) and Community Psychology, remains limited. To address this gap, our study investigates how the synergistic perspectives of PIO and Community Psychology contribute to our understanding of program strategies and governance within the Panggungharjo Village Government, with the ultimate goal of enhancing the welfare of its constituents. Employing a case study methodology, we analyze the data using Situational Analysis (SA). Data sources encompass in-depth interviews, focus group discussions (FGDs) involving key Panggungharjo village stakeholders, archival studies, and on-site observations. These diverse data are systematically coded and subjected to the principles of Situational Analysis (SA). This analytical approach not only seeks to uncover fundamental social processes but also illuminates the intricate relationships and interactions among the key elements operating within the field. The culmination of our findings takes the form of a